Bisphenol A alters the self-renewal and differentiation capacity of human bone-marrow-derived mesenchymal stem cells. (1st April 2016) - Strong, Amy L.; Miller, David F. B.; Buechlein, Aaron M.; Fang, Fang; Glowacki, Julie M.; McLachlan, John A.; Nephew, Kenneth P.; Burow, Matthew E.; Bunnell, Bruce A.
ABSTRACT: Bisphenol A (BPA) is an endocrine disruptor commonly used in industry to manufacture polycarbonate plastics. This endocrine disrupting chemical has been shown to mimic estrogens and has been associated with many serious health conditions. The effects of BPA on bone marrow derived mesenchymal stem cells (BMSCs) were investigated in vitro in the present study. BMSCs were exposed to BPA and assessed for proliferation and self-renewal capacity. The impact of BPA on osteogenic and adipogenic differentiation of BMSCs were also explored. Inhibitor studies were conducted to determine whether BPA alters BMSC biology through estrogen receptor (ER) signaling or MAPK signaling pathways. Although BMSCs treated with BPA demonstrated enhanced proliferation rate, BPA-treated BMSCs demonstrated a reduction in the total number of colony forming units (CFU); however, each CFU was larger (composed of more cells). BPA enhanced adipogenic differentiation of BMSCs, which correlated with increased mRNA expression levels for LEP, PPARG, and LPL following treatment with BPA. The administration of the mitogen-activated protein kinase (MAPK) pathway inhibitor PD184, 352 reversed the effects of BPA on proliferation and adipogenesis, whereas the treatment of the cells with ICI182, 780 blocked the effects of BPA on self-renewal and adipogenesis. Together, these results suggest that BPA markedly impacts BMSC biology, by enhancing proliferation through MAPK signaling, inhibiting self-renewal through ER signaling, and enhancing adipogenesis through both ER signaling or MAPK signaling.